Some anthropometric parameters applied in tooth size selection among filipinos - Valdez Jr., Victor Paul C.; Dominguez, Nannette (Adviser).; Ladao Jr., Joaquin (Adviser).
A study was made on 120 live subjects to determine the ratios between the measurements of certain cephalic landmarks and the size of anterior teeth. Eight parameters were used to verify certain ratios as it applied to the Filipinos. Consistency ranged from relatively less to higher level of consistency in others. The nasal width to the aggregate width of the maxillary incisors ratios found to be of particular significance.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.